Control of Risk in the Process Loading / Unloading In. Pelindo Iii Surabaya - Achmat Kuncoro1, Endang Dwiyanti1, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
PT. Pelindo III Surabaya is a company engaged in service providers. One of them is loading/unloading services. The results of preliminary observations made at PT. Pelindo III Surabaya shows that container loading/unloading workers do not follow standard operating procedures in the workplace such as not using safety helmets, safety vest, and safety shoes. Neat and dirty workplace conditions can increase potential hazards such as falls and tripping material and damage to the goods. This can threaten the safety and disturb the health of workers loading/unloading containers at PT. Pelindo III Surabaya. This study aims to analyze the risk assessment on loading/unloading work at PT. Pelindo III Surabaya. This research is an observational study with design crossectional. The study population was the workers in the loading/unloading section at PT. PELINDO III Surabaya as many as 20 people. Data that has been obtained from observations and interviews are processed and analyzed descriptively, namely by describing in real terms the object of research and the conditions at the research site. The results of the study show the process of loading/loading PT. PELINDO III Surabaya has 5 types of hazard risks in high-risk categories, 12 types of hazard risk, medium risk categories and 3 types of hazards in low-risk categories. The company is expected to provide and require workers to use body harnesses as additional PPE for workers who are above the container during the process cargo during.